Improving newborn skin health: Effects of diaper care regimens on skin pH and erythema. Issue 4 (31st May 2021) - Gustin, Jennifer; Bohman, Lisa; Ogle, Julie; Fadayel, Gina; Mitchell, Maria C.; Narendran, Vivek; Visscher, Marty O.; Carr, Andrew N.
Abstract: Background/Objective: Newborn infant skin is functional but immature, and diapering products can play a significant role in infant diapered skin health. Previous work demonstrated a regimen consisting of a diaper with an emollient and apertures on the inner liner (topsheet) with an acidic, pH‐buffered wipe (Regimen A) lowered newborn skin pH and reduced the enzymatic activity on skin post‐stool cleaning versus a regimen without these features (Regimen B). This study extends these findings to determine the impact of Regimen A on diaper area erythema severity over a 2‐week use period. Methods: This IRB‐approved, blinded, randomized, crossover study enrolled newborn infants >7 days and ≤8 weeks. Participants exclusively used two unique diaper and wipe combinations, Regimen A and Regimen B (non‐emollient, non‐aperture containing topsheet and wipe with limited buffering capacity), each for 14 days and preceded by a 3‐day washout regimen. Results: Diapered skin pH was reduced during Regimen A use to values similar to that of a non‐diapered control site (chest), while use of Regimen B was associated with a more alkaline skin pH. Regimen A resulted in significantly fewer severe erythema episodes. At the site of highest erythema, the perianal space, the average erythema score was significantly lower and more newborns were free of erythema while using Regimen A vs. Regimen B ( P < .05). Conclusions: These findings demonstrate that diapering products can have a significant impact on newborn skin. They reinforce the need to support the physiological normalization of skin pH and protection from skin irritation and damage.